Antimicrobial Activity of Calotropis procera Seeds - Bhaskar, V.H.; Ajay, S.S. (Asian Journal of Chemistry, 2010)
The present study is related to evaluate antimicrobial activities of chloroform and methanol extracts of seeds of Calotropis procera located in the forest area of Ghaziabad, India. Chloroforms extract of Calotropis procera seeds exhibited better antimicrobial activity. On the other hand, the extracts obtained Calotropis procera seeds tested have been evaluated for their possible in vitro antibacterial activities based on paper disc method.